Pembrolizumab with or without radiation therapy for metastatic non-small cell lung cancer: a randomized phase I/II trial. Issue 2 (13th October 2020) - Welsh, James; Menon, Hari; Chen, Dawei; Verma, Vivek; Tang, Chad; Altan, Mehmet; Hess, Kenneth; de Groot, Patricia; Nguyen, Quynh-Nhu; Varghese, Rejani; Comeaux, Nathan I; Simon, George; et al.
Abstract : Background: In this phase I/II trial, we evaluated the safety and effectiveness of pembrolizumab, with or without concurrent radiotherapy (RT), for lung and liver lesions from metastatic non-small cell lung cancer (mNSCLC). Methods: Patients with lung or liver lesions amenable to RT plus at least one additional non-contiguous lesion were included regardless of programmed death-ligand 1 (PD-L1) status. Pembrolizumab was given at 200 mg every 3 weeks for up to 32 cycles with or without concurrent RT. Metastatic lesions were treated with stereotactic body RT (SBRT; 50 Gy in 4 fractions) if clinically feasible or with traditionally fractionated RT (45 Gy in 15 fractions) if not. The primary end point was the best out-of-field lesion response, and a key secondary end point was progression-free survival (PFS). Results: The median follow-up time was 20.4 months. One hundred patients (20 phase I, 80 phase II) were evaluable for toxicity, and 72 phase II patients were evaluable for treatment response. No patients in the phase I group experienced grade 4–5 events; in the phase II group, two had grade 4 events and nine had grade 3 events. The ORR in the combined-modality cohort (irrespective of RT schema) was 22%, vs 25% in the pembrolizumab group (irrespective of receipt of salvage RT) (p=0.99). In the concurrent pembrolizumab+RT groups, the out-of-field ORRs were 38% in the pembrolizumab+SBRT group and 10% in the pembrolizumab+traditional RT group. When examining the pembrolizumab-alone patients, the out-of-field ORRs were 33% in those designated to receive salvage SBRT (if required) and 17% for salvage traditional RT. In all patients, the median PFS for pembrolizumab alone was 5.1 months (95% CI 3.4 to 12.7 months), and pembrolizumab/RT (regardless of schema) was 9.1 months (95% CI 3.6 to 18.4 months) (p=0.52). An exploratory analysis revealed that for patients with low PD-L1 expression, the median PFS was 4.6 vs 20.8 months for pembrolizumab with and without RT, respectively (p=0.004). Conclusions: Concurrent immunoradiotherapy for mNSCLC is safe, although larger trials are required to address which patients benefit most from RT. Trial registration number: NCT02444741 .